2017
DOI: 10.3389/fphys.2017.00931
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Noise-Evoked Excitation and Inhibition in Awake Mice CA3

Abstract: The hippocampus is known as a neuronal structure involved in learning, memory and spatial navigation using multi-sensory cues. However, the basic features of its response to acoustic stimuli without any behavioral tasks (conditioning) remains poorly studied. Here, we investigated the CA3 response to auditory stimuli using in vivo loose-patch recordings in awake and anesthetized C57 mice. Different acoustic stimuli in addition to broadband noise such as click, FM sound and pure tone were applied to test the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(76 reference statements)
0
11
0
2
Order By: Relevance
“…This pathway is implicated in the formation of long-term auditory memories [10], and auditory cues can be used in the formation of spatial memories [11]. Hippocampal place cells can be activated by a task using auditory dimension cues [12] and recently it was demonstrated that sound stimulation evoke excitatory and inhibitory currents in CA3 pyramidal neurons in vivo [13].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway is implicated in the formation of long-term auditory memories [10], and auditory cues can be used in the formation of spatial memories [11]. Hippocampal place cells can be activated by a task using auditory dimension cues [12] and recently it was demonstrated that sound stimulation evoke excitatory and inhibitory currents in CA3 pyramidal neurons in vivo [13].…”
Section: Introductionmentioning
confidence: 99%
“…We found increased c-fos expression in the pyramidal layer, were the glutamatergic pyramidal neurons are located, however we cannot discard the activation of GABAergic interneurons located in the pyramidal layer or adjacent to it. Interestingly, in vivo hippocampal recordings showed that sound exposure evokes inhibitory currents on pyramidal neurons, accordingly to the activation of hippocampal inhibitory interneurons (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus receives sensory information from several modalities, which are fundamental for its role in spatial navigation, learning and memory formation (Save et al, 2000;Jeffery, 2007;Ravassard et al, 2013). It is connected to the auditory system (Kraus and Canlon, 2012;Zhang et al, 2018) and sound stimulation triggers excitatory and inhibitory neurotransmission in hippocampal neurons in vivo (Wang et al, 2017). Also, the hippocampus is related to the formation of auditory memories (Squire et al, 2001), it uses auditory information for the formation of spatial memory (Tamura et al, 1990) and hippocampal place cells can be activated by auditory dimension cues (Aronov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Abe e colaboradores em 2014 já haviam demostrado que neurônios piramidais registrados in vivo no modo wholle cell patch clamp apresentaram hiperpolarização concomitante a estimulação com tons puros com 110 dB durante 300 ms em intervalos de 6-8 segundos. Além disso, registros in vivo em animais acordados mostraram que a estimulação sonora produz correntes sináptica inibitórias e excitatórias em neurônios piramidais da região CA3 do hipocampo (Wang et al, 2017) demostrando a responsividade direta do hipocampo a estimulação auditiva.…”
Section: Hipocampo E Sua Interação Com O Sistema Auditivounclassified